2015
DOI: 10.1007/s12206-015-0901-8
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic modeling and analysis for transmission system of high-power wind turbine gearbox

Abstract: As a key component to adjust the speed and torque, double-fed speed up gearbox plays a vital role in reliability and stability for the wind turbine system. Considering the base helix angle, normal pressure angle, position angle, rotation of carrier and the mesh of the ring gear and planet gear, a coupled dynamic model for high-power wind turbine gearbox transmission system, which consists of two helical planetary stages and one helical gear stage was established using the lumped parameter method in this paper.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Hu et al 13 established a load sharing model for planetary gear transmission system. Zhai et al 14 presented a dynamic model of high-speed gearbox of wind power turbine. Parker and Lin 15 provided an analytical model to study the necessary relationships to properly incorporate mesh phasing.…”
Section: Introductionmentioning
confidence: 99%
“…Hu et al 13 established a load sharing model for planetary gear transmission system. Zhai et al 14 presented a dynamic model of high-speed gearbox of wind power turbine. Parker and Lin 15 provided an analytical model to study the necessary relationships to properly incorporate mesh phasing.…”
Section: Introductionmentioning
confidence: 99%
“…It should be indicated that the wheel gear of the torque‐implement stage is identical with the wheel gear of the high‐speed stage. The corner mark of the pinion gear for the torque‐implement stage is ppT , reference listed the meaning of other corner marks of the parallel stage. Damping terms are neglected.…”
Section: Dynamics Model and Parameters Of The Transmission Systemmentioning
confidence: 99%
“…Many researchers focused on the design and the transmission characteristics of the conventional wind turbine gearbox for the double‐fed type wind turbine. The conventional wind turbine gearbox of the double‐fed type wind turbine has different transmission structures, such as two planetary gear transmission stages plus one parallel gear transmission stage, one planetary gear transmission stage plus two parallel gear transmission stages and flexible‐pins type transmission structure . Some wind turbine gearboxes have only two planetary gear transmission stages .…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, Zhai et al proposed a virtual prototype modelling method of hydraulic torque converter, shift clutch and vehicle transmission system with locking function. According to the structure and principle of hydraulic mechanical transmission system widely used in vehicle transmission, the model was analyzed and the dynamic model was established [7].…”
Section: Literature Reviewmentioning
confidence: 99%